Decontamination effect of hot-air drying against bacterial pathogen and surrogate strains on basil leaves, from laboratory to pilot scale settings. (March 2020) - Zhou, Zijin; Zuber, Sophie; Campagnoli, Matteo; Moser, Mireille; Devlieghere, Frank; Uyttendaele, Mieke
Abstract: Drying technologies are often evaluated on their efficiency to remove moisture and impact on sensory quality of products. The decontamination effect against foodborne pathogens, however, is rarely investigated. This study investigated the inactivation of foodborne pathogens and surrogates on basil leaves during drying, from characterizing thermal resistance of strains in aw -adjusted basil to collecting decontamination data under various drying processes. Salmonella Senftenberg was the most resistant pathogenic strain tested during heating on basil leaves. A treatment of 20 min at 60 °C reduced S. Senftenberg by 4.7 and 3.7-log on basil leaves at water activity of 0.99 and 0.95, respectively. The pronounced increase in strains' thermal resistance at reduced water activity was also observed during dynamic hot-air drying. Overall, more than 4-log reduction of S. Senftenberg was achieved after 90 min, 40 min and 20 min drying in a laboratory oven at 60 °C, 80 °C and 100 °C, respectively. Upscaling experiments in a pilot dryer using surrogate strains provided additional confirmation on the decontamination efficiency and effect of product moisture content during drying. Results from surrogate strains suggested that Escherichia coli P1 showed to be a more suitable surrogate for hot-air drying processes of basil leaves than Enterococcus faecium . Highlights: Hot-air drying at > 60 °C reduced Salmonella Senftenberg by 4-log on basil leaves. Product moisture content influenced the inactivation effect of drying substantially. E. coli P1 was the most suitable surrogate to validate hot-air drying processes. Decontamination effect of drying was validated from lab to pilot scale settings.